When Stiffness Matters: Mechanosensing in Heart Development and Disease - Gaetani, Roberto; Zizzi, Eric Adriano; Deriu, Marco Agostino; Morbiducci, Umberto; Pesce, Maurizio; Messina, Elisa (Frontiers in Cell and Developmental Biology, 2020)
During embryonic morphogenesis, the heart undergoes a complex series of cellular phenotypic maturations (e.g. transition of myocytes from proliferative to quiescent; maturation of the contractile apparatus), and this involves stiffening of the extracellular matrix acting in concert with morphogenetic signals. The maladaptive remodelling of the myocardium, one of the processes involved in determination of heart failure, also involve mechanical cues, with a progressive stiffening of the tissue that produces cellular mechanical damage, inflammation and ultimately myocardial fibrosis. Assessment of mechanical-dependent molecular machinery (in myocardial and non-myocardial cells) is therefore essential to contextualize the maturation of the cardiac tissue at early stages and understand its pathologic evolution in ageing. Since systems to perform multiscale modelling of cellular and tissue mechanics have been evolved, it appears particularly novel to design integrated mechano-molecular models of heart development and disease to be tested in ex vivo reconstituted cells/tissue-mimicking conditions. In the present contribution, we will discuss the latest implication of mechanosensing in heart development and pathology, describe the most recent models of cell/tissue mechanics and delineate novel strategies to target the consequences of heart failure with personalized approaches based on tissue engineering and iPSCs technologies.